2002
DOI: 10.1034/j.1398-9995.2002.03322.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE‐mediated anaphylaxis to Thiomucase®, a mucopolyssacharidase: allergens and cross‐reactivity

Abstract: An IgE-mediated anaphylaxis to Thiomucase is documented. Multiple allergens are recognized in Thiomucase by the patient serum, the main with 43 kDa. Partial cross-reactivity with BSA, cat dander and sheep dander is documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It has been shown that the target molecule of SJ18 ε 1, a monoclonal IgE antibody to Schistosoma japonicum that induces significant protection toward a challenge infection, was a paramyosin and that the target epitope was common among paramyosins of S. mansoni, Taenia solium, and E. granulosus (105). Cross-reactivity with more distant molecules is suggested by the recent clinical observation of IgE-mediated anaphylaxis to Thiomucase ® , a mucopolysaccharidase of sheep origin, used in the treatment of joint disorders (106). In this patient treated with Thiomucase, positive prick tests and specific IgE were found using BSA, cat, and sheep allergens, but also E. granulosus extracts.…”
Section: Characterization Of Echinococcus Sp Allergensmentioning
confidence: 81%
“…It has been shown that the target molecule of SJ18 ε 1, a monoclonal IgE antibody to Schistosoma japonicum that induces significant protection toward a challenge infection, was a paramyosin and that the target epitope was common among paramyosins of S. mansoni, Taenia solium, and E. granulosus (105). Cross-reactivity with more distant molecules is suggested by the recent clinical observation of IgE-mediated anaphylaxis to Thiomucase ® , a mucopolysaccharidase of sheep origin, used in the treatment of joint disorders (106). In this patient treated with Thiomucase, positive prick tests and specific IgE were found using BSA, cat, and sheep allergens, but also E. granulosus extracts.…”
Section: Characterization Of Echinococcus Sp Allergensmentioning
confidence: 81%
“…SAs are minor allergens in animal dander and in milk but major allergens in meats. In view of the reported cross-reactivity between SAs from mammals, even if they are phylogenetically distinct [41], the diagnostic work-up in meat-allergic individuals should always include tests with meats from different mammals, and the use of alternative meats should always be carefully evaluated on an individual basis. Furthermore, due to cross-reactivity phenomena, children with persistent milk allergy and BSA sensitization show an increased risk of clinically relevant sensitization to animal dander [14].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactivity seemed to be relevant as many antigens, including cyclophyllin of birch pollen, Malassezia furfur , Shistosomia japonica and Strongiloides stercoralis have been shown to cross-react with one of the antigens of E. granulosus [20, 21]. Cross-reactivity was also determined on thiomucase, a drug including mucopolysaccharidase of sheep origin, with cat, sheep and E. granulosus extracts [22]. Furthermore, cross-reactivity of streptococcal cell wall antigens with Mycobacterium tuberculosis was demonstrated with T cell lines [23].…”
Section: Discussionmentioning
confidence: 99%